A comparison of three outcome measures of the impact of vasomotor symptoms on women's lives. (4th July 2019) - Hunter, M. S.; Nuttall, J.; Fenlon, D.
Abstract: Objective: Measures of the impact of vasomotor symptoms (VMS) have been used as outcomes in clinical trials but have not been compared. This study compares the Hot Flush Rating Scale (HFRS), the Hot Flash Related Daily Interference Scale (HFRDIS), and the shorter Hot Flash Interference (HFI) scale. Methods: Baseline data were taken from two studies including healthy women (menopause transition or postmenopause) and breast cancer patients experiencing VMS. Participants completed questionnaires on sociodemographics, the HFRS, the HFRDIS, the HFI, the Work and Social Adjustment Scale (WSAS), on depression (Generalized Anxiety Disorder 7), on anxiety (Patient Health Questionnaire 9), and on use of medical services. Results: A total of 169 women (129 with history of breast cancer and 40 without) aged 54.47 (standard deviation [SD] = 9.11) years took part. They had an average of 66 (SD = 40.94) VMS per week, with a mean HFRS problem-rating of 6.53 (SD = 1.99), HFRDIS score of 5.36 (SD = 2.22), and HFI score of 6.13 (SD = 2.30). The HFRS problem-rating, HFRDIS, and HFI were significantly associated ( r  = 0.61–0.85), had good internal reliability (α = 0.76–0.91), and had significant concurrent validity with mood, the WSAS, and use of medical services. VMS frequency was not associated with mood, the WSAS, or use of medical services. Conclusion: The HFRS problem-rating scale and the HFI are two brief, three-item measures that measure a similar concept of VMS interference/impact, with evidence of reliability and validity.